An Overview of Ultra-Wide-Band Systems With MIMO - Kaiser, Thomas; Zheng, Feng; Dimitrov, Emil (Proceedings of the IEEE, 2009)
Ultra-wide-band (UWB) technology combined with multiple transmit and receive antennas (MIMO) is a viable way to achieve data rates of more than 1 Gb/s for wireless communications. UWB is typically applied to short-range and therefore mainly indoor communications in environments characterized usually by dense multipath propagation. For this type of environment, MIMO systems allow for a substantial increase of spectral efficiency by exploiting the inherent array gain and spatial multiplexing gain of the systems. In this paper, we provide a brief overview for UWB-MIMO wireless technology. The overview covers channel capacity, space-time coding (STC), and beamforming. It is shown that the spectral efficiency is increased logarithmically and linearly , respectively, for single transmit and multiple receive antennas (SIMO) and MIMO systems. For multiple transmit and single receive antenna (MISO) systems, a threshold for the data transmission rate exists such that the spatial multiplexing gain can be obtained if the data rate is lower than this threshold, but it is not beneficial to deploy multiple transmit antennas if the required data rate is higher than the threshold. Two STC schemes for UWB-MIMO are briefly discussed, and their performance comparison is presented. A discussion about antenna selection is also presented, and the performance comparison between antenna selection and equal gain combiner is provided showing the diversity gain for some scenarios. For the beamforming, it is shown that the optimal beamformer is obtained if all the weighting filters in each antenna branch are identical. About the optimal beamformer, it is found that the amplitude of the side lobe is independent of the ray incidence angle, and the amplitude of the main lobe is increased by a fold of the element number in the array. Three kinds of beam patterns are defined, and the beamwidth of the main lobe is given. Experimental results based on an offline testbed are provided to verify some analytical results presented in this paper. Since UWB-MIMO is still in its research infancy, the aim of this paper is to present some first results on spatial multiplexing, STC, and beamforming to illustrate the potential of UWB-MIMO.